Developing language teacher identity and leadership skills in intercultural learning environments - Elbwart, Katharina; Keatinge, Dagmar (Language Teacher Leadership. Insights from Research and Practice.)

MAAS: Hiding Trojans in Approximate Circuits - Ahmed, Qazi Arbab; Awais, Muhammad; Platzner, Marco (2023 24th International Symposium on Quality Electronic Design (ISQED))

Talentsuche im paralympischen Sport (ParaTalent) - Radtke, Sabine; Vogel, Alina
Keywords: Para Sport; Talentmaßnahmen; Nachwuchs

The Consumerization of Care: How Capitalism Is Co-Opting Solidarity - Alberternst, B.; Giesler, M.; Steinhoff, Lena; Eggert, A.

Life Cycle Assessment of Lightweight Structures in Vehicles for New Mobility Concepts - Ostermann, Moritz; Dierkes, Eric; Marten, Thorsten; Tröster, Thomas (Proceedings of the 18th Conference on Sustainable Development of Energy, Water and Environmental Systems, Dubrovnik, Croatia 2023)

Electrochemical Sodium Storage in Hard Carbon Powder Electrodes Implemented in an Improved Cell Assembly: Insights from In-Situ and Ex-Situ Solid-State NMR - Šić, Edina; Schutjajew, Konstantin; Haagen, Ulrich; Breitzke, Hergen; Oschatz, Martin; Buntkowsky, Gerd; Gutmann, Torsten (Chemsuschem)
Abstract In this work, we report on an improved cell assembly of cylindrical electrochemical cells for 23Na in-situ solid-state NMR (ssNMR) investigations. The cell set-up is suitable for using powder electrode materials. Reproducibility of our cell assembly is analyzed by preparing two cells containing hard carbon (HC) powder as working electrode and sodium metal as reference electrode. Electrochemical storage properties of HC powder electrode derived from carbonization of sustainable cellulose are studied by ssNMR. 23Na in-situ ssNMR monitors the sodiation/desodiation of a Na{|}NaPF6{|}HC cell (cell 1) over a period of 22?days, showing high cell stability. After the galvanostatic process, the HC powder material is investigated by high resolution 23Na ex-situ MAS NMR. The formation of ionic sodium species in different chemical environments is obtained. Subsequently, a second Na{|}NaPF6{|}HC cell (cell 2) is sodiated for 11?days achieving a capacity of 220?mAh/g. 23Na ex-situ MAS NMR measurements of the HC powder material extracted from this cell clearly indicate the presence of quasi-metallic sodium species next to ionic sodium species. This observation of quasi-metallic sodium species is discussed in terms of the achieved capacity of the cell as well as of side reactions of sodium in this electrode material.
Keywords: solid-state nmr; hard carbon; electrochemical cells; in-situ characterization; sodium

SiCO Ceramics as Storage Materials for Alkali Metals/Ions: Insights on Structure Moieties from Solid-State NMR and DFT Calculations - Šić, Edina; Rohrer, Jochen; Ricohermoso, Emmanuel; Albe, Karsten; Ionescu, Emmanuel; Riedel, Ralf; Breitzke, Hergen; Gutmann, Torsten; Buntkowsky, Gerd (Chemsuschem)
Abstract Polymer-derived silicon oxycarbide ceramics (SiCO) have been considered as potential anode materials for lithium- and sodium-ion batteries. To understand their electrochemical storage behavior, detailed insights into structural sites present in SiCO are required. In this work, the study of local structures in SiCO ceramics containing different amounts of carbon is presented. 13C and 29Si solid-state MAS?NMR spectroscopy combined with DFT calculations, atomistic modeling, and EPR investigations, suggest significant changes in the local structures of SiCO ceramics even by small changes in the material composition. The provided findings on SiCO structures will contribute to the research field of polymer-derived ceramics, especially to understand electrochemical storage processes of alkali metal/ions such as Na/Na+ inside such networks in the future.
Keywords: NMR spectroscopy; Ceramics; defects; density functional calculations; EPR spectroscopy

Collaborative Mechanistic Effects between Vanadia and Titania during the Oxidative Dehydrogenation of Propane Investigated by Operando and Transient Spectroscopies - Schumacher, Leon; Pfeiffer, Johannes; Shen, Jun; Gutmann, Torsten; Breitzke, Hergen; Buntkowsky, Gerd; Hofmann, Kathrin; Hess, Christian (ACS Catalysis)
The oxidative dehydrogenation (ODH) of propane is of great technical importance, and supported VOx catalysts have shown promising properties for the reaction. One of the most prominent and active supports is titania, which exhibits a high activity but many questions regarding the catalyst system are still in debate. In this study, we elucidate the mechanism of the propane ODH reaction over VOx/TiO2, using P25 and ALD (atomic layer deposition) synthesized TiO2/SBA-15 as a support, with X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), 51V solid-state (ss)NMR, operando multiwavelength Raman, operando UV–vis, and transient IR spectroscopies. Bare titania shows a small conversion, leading to carbon formation, and the reaction occurs at the interface between anatase and rutile. In comparison, in VOx/TiO2 catalysts, the activity shifts from titania to vanadia sites. UV-Raman spectroscopy and structural characterization data revealed the reaction to involve preferentially the V═O bonds of dimeric species rather than doubly bridged V–O–V bonds, which leads to higher propene selectivities. The active vanadium site shows a nuclearity-dependent behavior; that is, at higher loadings, when oligomeric vanadia is present, it shifts from V═O bonds to linear V–O–V bonds in oligomers, leading to less selective oxidation due to the better reducibility. Our operando/transient spectroscopic results demonstrate the direct participation of the titania support in the reaction by influencing the degree of vanadia oligomerization and enabling rapid hydrogen transfer from propane to vanadia via Ti–OH groups on anatase, accelerating the rate-determining step of the initial C–H bond breakage. The broader applicability of the results is confirmed by the behavior of the ALD-synthesized sample, which resembles that of P25. Our results highlight the detailed level of mechanistic understanding accessible from multiple spectroscopic approaches, which can be readily transferred to other materials and/or reactions. The oxidative dehydrogenation (ODH) of propane is of great technical importance, and supported VOx catalysts have shown promising properties for the reaction. One of the most prominent and active supports is titania, which exhibits a high activity but many questions regarding the catalyst system are still in debate. In this study, we elucidate the mechanism of the propane ODH reaction over VOx/TiO2, using P25 and ALD (atomic layer deposition) synthesized TiO2/SBA-15 as a support, with X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), 51V solid-state (ss)NMR, operando multiwavelength Raman, operando UV–vis, and transient IR spectroscopies. Bare titania shows a small conversion, leading to carbon formation, and the reaction occurs at the interface between anatase and rutile. In comparison, in VOx/TiO2 catalysts, the activity shifts from titania to vanadia sites. UV-Raman spectroscopy and structural characterization data revealed the reaction to involve preferentially the V═O bonds of dimeric species rather than doubly bridged V–O–V bonds, which leads to higher propene selectivities. The active vanadium site shows a nuclearity-dependent behavior; that is, at higher loadings, when oligomeric vanadia is present, it shifts from V═O bonds to linear V–O–V bonds in oligomers, leading to less selective oxidation due to the better reducibility. Our operando/transient spectroscopic results demonstrate the direct participation of the titania support in the reaction by influencing the degree of vanadia oligomerization and enabling rapid hydrogen transfer from propane to vanadia via Ti–OH groups on anatase, accelerating the rate-determining step of the initial C–H bond breakage. The broader applicability of the results is confirmed by the behavior of the ALD-synthesized sample, which resembles that of P25. Our results highlight the detailed level of mechanistic understanding accessible from multiple spectroscopic approaches, which can be readily transferred to other materials and/or reactions.

Peptides as Model Systems for Biofunctionalizations of Cellulose─Synthesis and Structural Characterization by Advanced Solid-State Nuclear Magnetic Resonance Techniques - Limprasart, Waranya; Höfler, Mark Valentin; Kunzmann, Nico; Rösler, Lorenz; Herr, Kevin; Breitzke, Hergen; Gutmann, Torsten (The Journal of Physical Chemistry C)
The tailored design of bioactive materials based on cellulose or paper is still a challenging task. It requires detailed knowledge of the structure and interaction of the biofunctionalization with the carrier material at the nanoscale. In this work, the small peptide sequence Acetyl-Pro-Ala-Phe-Gly-OH (peptide 1) that can serve as a model for biofunctionalization is synthesized via solid-phase peptide synthesis, purified, and characterized by high-performance liquid chromatography (HPLC) and mass spectrometry (MS). The as-obtained peptide is bound to microcrystalline cellulose (MCC) via a wet chemical approach. Quantification of the peptide on the MCC carrier is performed by replacing l-proline (Pro) in the peptide sequence by 4-fluoro-l-proline (Pro(19F)) (peptide 2) and applying 19F magic angle spinning nuclear magnetic resonance (MAS NMR). Detailed characterization of the model system is provided by using 1H → 13C cross-polarization magic angle spinning (CP MAS NMR) combined with dynamic nuclear polarization (DNP) to enhance sensitivity. Analysis of the binding of the peptide on MCC necessitates the replacement of l-glycine (Gly) in the sequence by 13C-labeled l-glycine (Gly(13C)) (peptide 3). DNP-enhanced 13C–13C correlation experiments carried out with dipolar assisted rotational resonance (DARR) are then used to analyze the proximity between the model peptide and the MCC carrier. The strength of the dipolar coupling is estimated from the DNP-enhanced 1H → 13C CP MAS double-quantum rotational resonance (DQrotres) experiment. The obtained dipolar coupling between the 13C═O carbon of peptide 3 and the C6 carbon of the cellulose is equal to a carbon–carbon distance of about two C–O bond lengths, which strongly suggests the binding of significant amounts of the peptide on MCC via an ester bond. The tailored design of bioactive materials based on cellulose or paper is still a challenging task. It requires detailed knowledge of the structure and interaction of the biofunctionalization with the carrier material at the nanoscale. In this work, the small peptide sequence Acetyl-Pro-Ala-Phe-Gly-OH (peptide 1) that can serve as a model for biofunctionalization is synthesized via solid-phase peptide synthesis, purified, and characterized by high-performance liquid chromatography (HPLC) and mass spectrometry (MS). The as-obtained peptide is bound to microcrystalline cellulose (MCC) via a wet chemical approach. Quantification of the peptide on the MCC carrier is performed by replacing l-proline (Pro) in the peptide sequence by 4-fluoro-l-proline (Pro(19F)) (peptide 2) and applying 19F magic angle spinning nuclear magnetic resonance (MAS NMR). Detailed characterization of the model system is provided by using 1H → 13C cross-polarization magic angle spinning (CP MAS NMR) combined with dynamic nuclear polarization (DNP) to enhance sensitivity. Analysis of the binding of the peptide on MCC necessitates the replacement of l-glycine (Gly) in the sequence by 13C-labeled l-glycine (Gly(13C)) (peptide 3). DNP-enhanced 13C–13C correlation experiments carried out with dipolar assisted rotational resonance (DARR) are then used to analyze the proximity between the model peptide and the MCC carrier. The strength of the dipolar coupling is estimated from the DNP-enhanced 1H → 13C CP MAS double-quantum rotational resonance (DQrotres) experiment. The obtained dipolar coupling between the 13C═O carbon of peptide 3 and the C6 carbon of the cellulose is equal to a carbon–carbon distance of about two C–O bond lengths, which strongly suggests the binding of significant amounts of the peptide on MCC via an ester bond.

The Rapid Mechanochemical Synthesis of Microporous Covalent Triazine Networks: Elucidating the Role of Chlorinated Linkers by a Solvent-Free Approach - Krusenbaum, Annika; Kraus, Fabien Joel Leon; Hutsch, Stefanie; Grätz, Sven; Höfler, Mark Valentin; Gutmann, Torsten; Borchardt, Lars (Advanced Sustainable Systems)
Abstract The mechanochemical synthesis of porous covalent triazine networks (CTNs), exhibiting theoretically ideal C/N ratios and high specific surface areas, is presented. Employing this solvent-free approach allows to minimize the ecological impact of the synthesis by bypassing hazardous wastes, while simultaneously observing the reactions between the individual starting materials separately for the first time. Especially the role of dichloromethane needs to be reconsidered, functioning as a linker between the nitrogen-containing node cyanuric chloride and the aromatic monomer 1,3,5-triphenylbenzene, as proven by X-ray photoelectron spectroscopy and 1H â†’ 13C Cross-Polarization magic-angle-spinning nuclear magnetic resonance spectroscopy. This results in a drastic enhancement of the reaction rate, reducing the synthesis time down to 1 minute. Additionally, this linkage over a C1 bridge enables the incorporation of nitrogen into already synthesized polymers by post polymerization functionalization. The variation of the synthesis building blocks, namely the linker, node, and monomer, results in a variety of nitrogen-containing polymers with specific surface areas of up to 1500 m2 gâˆ’1. Therefore, the presented approach is capable to target the synthesis of various CTNs with a minimal use of chlorinated linker, rendering the concept as a sustainable alternative to the classical solution-based synthesis.

Solute–Solvent Interactions of 2,2,6,6-Tetramethylpiperidinyloxyl and 5-Tert-Butylisophthalic Acid in Polyethylene Glycol as Observed by Measurements of Density, Viscosity, and Self-Diffusion Coefficient - Hoffmann, Markus M.; Randall, Nathaniel P.; Apak, Miray H.; Paddock, Nathaniel A.; Gutmann, Torsten; Buntkowsky, Gerd (Journal of Solution Chemistry)
This study is seeking a better understanding of polyethylene glycol (PEG) as a solvent to promote its use in chemical synthesis. The effect of adding two solutes of interest, 2,2,6,6-tetramethylpiperidinyloxyl (TEMPO) and 5-tert-butylisophthalic acid (5-TBIPA) to PEG200 (average molar weight of 200 g·mol−1) on the solution density, viscosity, and self-diffusion coefficients is monitored in a temperature range of 298.15–358.15 K to deduce how these solutes interact with the PEG200 solvent. The effect of water, the most common impurity in PEGs, is also monitored and found to be nearly negligibly small. Addition of (5-TBIPA) increases solution density and viscosity. Combined with the observation that 5-TBIPA consistently self-diffuses at about half the rate as PEG200 at all investigated experimental conditions, this suggests strong attractive solute–solvent interactions likely through hydrogen bonding interactions. In contrast, addition of TEMPO causes lower solution densities and viscosities suggesting that the solute–solvent interactions of TEMPO lead to an overall weakening of the intermolecular interactions present compared to neat PEG200. Inspection of the viscosity and self-diffusion temperature dependence reveals slight deviations from the Arrhenius equation. Interestingly, the activation energies obtained from the viscosity and the self-diffusion data are essentially identical in values suggesting that the same dynamic processes and thus the same activation barriers govern translational motion and momentum transfer in these PEG200 solutions.

Fluorine-Labeled N-Boc-l-proline as a Marker for Solid-State NMR Characterization of Biofunctionalizations on Paper Substrates - Höfler, Mark V.; Limprasart, Waranya; Rösler, Lorenz; Fleckenstein, Max; Brodrecht, Martin; Herr, Kevin; Schäfer, Jan-Lukas; Biesalski, Markus; Breitzke, Hergen; Gutmann, Torsten (Journal of Physical Chemistry C)
An efficient approach employing 4-dimethylaminopyridine and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride as the coupling reagent is presented, which enables the functionalization of cotton linter paper substrates with the 19F spin label N-boc-cis-4-fluoro-l-proline. This spin label can be easily quantified by 19F magic angle spinning (MAS) NMR experiments to determine its loading on paper substrates. During the functionalization, the spin label stays intact, as confirmed by the 1Hâ€“19F heterocorrelation (1HÂ â†’Â 19F CP MAS FSLG HETCOR) experiments. In combination with dynamic nuclear polarization (19F MAS DNP), the N-boc-cis-4-fluoro-l-proline spin label allows us to inspect 1 Î¼mol/g and even lower molecule loadings on paper substrates, providing a highly sensitive local probe to analyze the structure of biofunctionalizations at the nanoscale on paper substrates in the future. An efficient approach employing 4-dimethylaminopyridine and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride as the coupling reagent is presented, which enables the functionalization of cotton linter paper substrates with the 19F spin label N-boc-cis-4-fluoro-l-proline. This spin label can be easily quantified by 19F magic angle spinning (MAS) NMR experiments to determine its loading on paper substrates. During the functionalization, the spin label stays intact, as confirmed by the 1Hâ€“19F heterocorrelation (1HÂ â†’Â 19F CP MAS FSLG HETCOR) experiments. In combination with dynamic nuclear polarization (19F MAS DNP), the N-boc-cis-4-fluoro-l-proline spin label allows us to inspect 1 Î¼mol/g and even lower molecule loadings on paper substrates, providing a highly sensitive local probe to analyze the structure of biofunctionalizations at the nanoscale on paper substrates in the future.

Influence of APTES-Decorated Mesoporous Silica on the Dynamics of Ethylene Glycol Molecules─Insights from Variable Temperature 2H Solid-State NMR - Haro Mares, Nadia B.; Brodrecht, Martin; Wissel, Till; Döller, Sonja C.; Rösler, Lorenz; Breitzke, Hergen; Hoffmann, Markus M.; Gutmann, Torsten; Buntkowsky, Gerd (The Journal of Physical Chemistry C)
The physicochemical effects of decorating pore walls of high surface area materials with functional groups are not sufficiently understood, despite the use of these materials in a multitude of applications such as catalysis, separations, or drug delivery. In this study, the influence of 3-amino-propyl triethoxysilane (APTES)-modified SBA-15 on the dynamics of deuterated ethylene glycol (EG-d4) is inspected by comparing three systems: EG-d4 in the bulk phase (sample 1), EG-d4 confined in SBA-15 (sample 2), and EG-d4 confined in SBA-15 modified with APTES (sample 3). The phase behavior (i.e., melting, crystallization, glass formation, etc.) of EG-d4 in these three systems is studied by differential scanning calorimetry. Through line shape analysis of the 2H solid-state NMR (2H ssNMR) spectra of the three systems recorded at different temperatures, two signal patterns, (i) a Lorentzian (liquid-like) and (ii) a Pake pattern (solid-like), are identified from which the distribution of activation energies for the dynamic processes is calculated employing a two-phase model. The physicochemical effects of decorating pore walls of high surface area materials with functional groups are not sufficiently understood, despite the use of these materials in a multitude of applications such as catalysis, separations, or drug delivery. In this study, the influence of 3-amino-propyl triethoxysilane (APTES)-modified SBA-15 on the dynamics of deuterated ethylene glycol (EG-d4) is inspected by comparing three systems: EG-d4 in the bulk phase (sample 1), EG-d4 confined in SBA-15 (sample 2), and EG-d4 confined in SBA-15 modified with APTES (sample 3). The phase behavior (i.e., melting, crystallization, glass formation, etc.) of EG-d4 in these three systems is studied by differential scanning calorimetry. Through line shape analysis of the 2H solid-state NMR (2H ssNMR) spectra of the three systems recorded at different temperatures, two signal patterns, (i) a Lorentzian (liquid-like) and (ii) a Pake pattern (solid-like), are identified from which the distribution of activation energies for the dynamic processes is calculated employing a two-phase model.

Direct and Indirect DNP NMR Uncovers the Interplay of Surfactants with Their Mesoporous Host Material - Döller, Sonja C.; Brodrecht, Martin; Gutmann, Torsten; Hoffmann, Markus; Buntkowsky, Gerd (The Journal of Physical Chemistry C)
Two different mesoporous silica materials (SBA-15 and MCM 41) were impregnated with four different, commercially available surfactants, namely, E5, PEG 200, C10E6, and Triton X-100. Differential scanning calorimetry was employed to confirm the confinement of the surfactants in the pores of their host materials. Dynamic nuclear polarization enhanced solid state 13C magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra were recorded for these materials, showing that both the direct as well as the indirect polarization transfer pathways are active for the carbons of the polyethylene glycol moieties of the surfactants. The presence of the indirect polarization pathway implies the presence of molecular motion with correlation times faster than the inverse Larmor frequency of the observed signals. The intensities of the signals were determined, and an approach based on relative intensities was employed to ensure comparability throughout the samples. From these data, the interactions of the surfactants with the pore walls could be determined. Additionally, a model describing the surfactants’ arrangement in the pores was developed. It was concluded that all carbons of the hydrophilic surfactants, E5 and PEG 200, interact with the silica walls in a similar fashion, leading to similar polarization transfer pathway patterns for all observed signals. For the amphiphilic surfactants C10E6 and Triton X-100, the terminal hydroxyl group mediates the majority of the interactions with the pore walls and the polarizing agent. Two different mesoporous silica materials (SBA-15 and MCM 41) were impregnated with four different, commercially available surfactants, namely, E5, PEG 200, C10E6, and Triton X-100. Differential scanning calorimetry was employed to confirm the confinement of the surfactants in the pores of their host materials. Dynamic nuclear polarization enhanced solid state 13C magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra were recorded for these materials, showing that both the direct as well as the indirect polarization transfer pathways are active for the carbons of the polyethylene glycol moieties of the surfactants. The presence of the indirect polarization pathway implies the presence of molecular motion with correlation times faster than the inverse Larmor frequency of the observed signals. The intensities of the signals were determined, and an approach based on relative intensities was employed to ensure comparability throughout the samples. From these data, the interactions of the surfactants with the pore walls could be determined. Additionally, a model describing the surfactants’ arrangement in the pores was developed. It was concluded that all carbons of the hydrophilic surfactants, E5 and PEG 200, interact with the silica walls in a similar fashion, leading to similar polarization transfer pathway patterns for all observed signals. For the amphiphilic surfactants C10E6 and Triton X-100, the terminal hydroxyl group mediates the majority of the interactions with the pore walls and the polarizing agent.

Higher rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, Lasse Lennart (Analysis & PDE)
For a compact Riemannian locally symmetric space $Γ\backslash G/K$ of arbitrary rank we determine the location of certain Ruelle-Taylor resonances for the Weyl chamber action. We provide a Weyl-lower bound on an appropriate counting function for the Ruelle-Taylor resonances and establish a spectral gap which is uniform in $Γ$ if $G/K$ is irreducible of higher rank. This is achieved by proving a quantum-classical correspondence, i.e. a 1:1-correspondence between horocyclically invariant Ruelle-Taylor resonant states and joint eigenfunctions of the algebra of invariant differential operators on $G/K$.

Meromorphic Continuation of Weighted Zeta Functions on Open Hyperbolic Systems - Schütte, Philipp; Weich, Tobias; Barkhofen, Sonja (Communications in Mathematical Physics)
In this article we prove meromorphic continuation of weighted zeta functions in the framework of open hyperbolic systems by using the meromorphically continued restricted resolvent of Dyatlov and Guillarmou (2016). We obtain a residue formula proving equality between residues of weighted zetas and invariant Ruelle distributions. We combine this equality with results of Guillarmou, Hilgert and Weich (2021) in order to relate the residues to Patterson-Sullivan distributions. Finally we provide proof-of-principle results concerning the numerical calculation of invariant Ruelle distributions for 3-disc scattering systems.

Explaining Face Recognition Through SHAP-Based Pixel-Level Face Image Quality Assessment - Biagi, Clara; Rethfeld, Louis; Kuijper, Arjan; Terhörst, Philipp (2023 IEEE International Joint Conference on Biometrics (IJCB))

A novel indexing algorithm for latent palmprints leveraging minutiae and orientation field - Khodadoust, Javad; Monroy, Raúl; Medina-Pérez, Miguel Angel; Loyola-González, Octavio; Kusakunniran, Worapan; Boller, André; Terhörst, Philipp (Intelligent Systems with Applications)

An EPR Study on Highly Stable Nitroxyl-Nitroxyl Biradicals for Dynamic Nuclear Polarization Applications at High Magnetic Fields - Asanbaeva, Nargiz B.; Dobrynin, Sergey A.; Morozov, Denis A.; Haro-Mares, Nadia; Gutmann, Torsten; Buntkowsky, Gerd; Bagryanskaya, Elena G. (Molecules)

Datenqualitätssicherung im Forschungsprozess am Beispiel von Zugversuchen - Müller, Laura; Wawer, Max Leo; Heimes, Norman; Uhe, Johanna; Koepler, Oliver; Auer, Sören; Lachmayer, Roland; Mozgova, Iryna (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))
Progressive digitization throughout the entire product data life cycle requires a more sensitive handling and understanding of data within engineering processes. Regarding engineering research data, the aim is to implement the FAIR data principles (Findable, Accessible, Interoperable, Reusable) to guarantee the post-usability of research data. To ensure the quality of data throughout the entire research process a methodical approach had been developed. Based on the quality categories Intrinsic, Representative, Contextual and Available, the related quality dimensions are considered differentiated along the research data life cycle and presented in a concept. As a use case, this concept is carried out on a tensile test with documentation of results in a research data management system.